HUBUNGAN STATUS GIZI DENGAN PERKEMBANGAN ANAK USIA PRA SEKOLAH DI CITA BUNDA SCHOOL DAN PG-TK KURNIA DJAJA ALAM KOTA BATAM - Sahreni, Sukma; Esmiralda, Nopri; Putri, Tasya Rizkia (Universitas Batam, 2024)
Background: Nutritional status is the state of the body that results from food or is a measure of success in fulfilling a diet. Children with acute malnutrition, experience protein deficiency which will have an impact on the weakness of small muscles so that it will be difficult to grow and develop. Developmental stages in children can be used as a means to detect or predict early developmental problems according to their age. The purpose of this study is to determine the relationship between nutritional status and the development of pre-school children at Cita Bunda School and PG-TK Kurnia Djaja Alam Batam City in 2023. Methods: This research design is an analytical research with a cross-sectional approach conducted at Cita Bunda School and PG-TK Kurnia Djaja Alam in November 2023. The sampling technique is total sampling with a total sample of 50 children. Data analysis used univariate analysis and biariat analysis with chi-square test. Results: The results of Chi-Square analysis for the relationship of nutritional status with the development of pre-school children obtained p = 0.001 (p < 0.05) which means Hₒ rejected and H₁ accepted. Conclusion: Based on the results of this study, it was found that there is a relationship between nutritional status and the development of pre-school children at Cita Bunda School and PG-TK Kurnia Djaja Alam Batam City.